Dyslexia: the quiet enemy can take control in the classroom - Euribe Salgado, Fiorella (2018)
Dyslexia is one of the main factors for which a child abandon school. A 5% of children between 7 and 9 years old, suffer from dyslexia, in addition, this means that each teacher has at least one child who struggle without support for accessto learning. This disorder affects directly to the reading, writing and speaking learning, but it also has emotional and conductual consequences which can lead into frustration and social adaptation problems. Because of these causes, it is tooimportant that teachers have resources and tools for detecting the disorder and helping to children, providing not only a way for accessing to learning unless enjoying of the process.